Millet Adoption in Bundelkhand, U.P.: Traditional vs. Emerging Crop Trends (Indian Journal of Extension Education, 2025)
The study, conducted between January and March 2023, investigated millet adoption patterns among 400 farmers in Bundelkhand, Uttar Pradesh, India, comparing traditional crop cultivation with emerging millet trends in Jalaun and Jhansi districts. The current study’s findings indicated that millets, driven by climate resilience (50%), market demand (37.5%), and nutritional value (12.5%), are cultivated by 37.5 per cent of farmers, while traditional crops (wheat, rice, maize) dominate (62.5%) due to market reliability. Millets are consumed daily by 10 per cent, primarily at breakfast (30%) and lunch (25%), enhancing nutritional security. Significant challenges to millet adoption include limited market access and awareness. ANOVA and Chi-square tests revealed significant differences in crop selection and consumption across gender (p<0.01), age (p<0.05), and income (p<0.05). However, adoption requires robust policy support, with significant positive correlations for climate resilience (p=0.03) and nutritional benefits (p=0.04), while market access constraints (p=0.02) showed negative correlations. Composite reliability values, ranging from 0.750 to 0.980, demonstrated strong internal consistency across measured constructs.